2014
DOI: 10.3892/mco.2014.321
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Bmi1 mRNA as a potential prognostic biomarker for distant metastasis in colorectal cancer patients

Abstract: Abstract. Bmi1 is overexpressed in gastrointestinal cancers, including colorectal cancer (CRC); however, its role as a non-invasive biomarker in CRC has not been established. The aim of this study was to compare the plasma Bmi1 mRNA levels prior to and following curative resection of the primary tumor in CRC patients and to determine their association with the clinicopathological parameters. The plasma Bmi1 mRNA level was measured by quantitative polymerase chain reaction and expressed as cycle threshold value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In addition, BMI1 polycomb ring finger oncogene—an intestinal stem cell marker that is overexpressed in various cancers [23]–was upregulated two-fold in E . faecalis + CRCs, which is striking since high expression of BMI1 is significantly associated with metastasis [24,25] and poor survival [26] in CRC patients. Importantly, aberrant BMI1 expression has been found in premalignant gastrointestinal lesions [23], which points to its possible role in cancer initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BMI1 polycomb ring finger oncogene—an intestinal stem cell marker that is overexpressed in various cancers [23]–was upregulated two-fold in E . faecalis + CRCs, which is striking since high expression of BMI1 is significantly associated with metastasis [24,25] and poor survival [26] in CRC patients. Importantly, aberrant BMI1 expression has been found in premalignant gastrointestinal lesions [23], which points to its possible role in cancer initiation.…”
Section: Discussionmentioning
confidence: 99%
“…48 In addition, another recent study reported that patients with decreased postoperative plasma mRNA levels of BMI1 compared to patients with increased postoperative mRNA levels correlated with a favorable prognosis in CRC. 49 These studies suggest that BMI1 may be of relevance as a prognostic indicator in CRC. However, the exact directionality of its prognostic utility remains to be elucidated.…”
Section: Bmi1mentioning
confidence: 97%
“…This suggests that the functional significance of BMI1 is maintenance of stem cell properties in colon cancer cells. Consistent with this notion, clinical studies report that BMI1 expression is a negative predictor in colon cancer [ 72 , 73 , 74 , 75 ].…”
Section: Methods To Detect Colon Cancer Stem Cellsmentioning
confidence: 71%